Cross Elasticity of Demand of Selected Wooden Furniture in Respect to Alternative Furniture in Chittagong City (The Chittagong University Journal of Science, 2022)
A large market of furniture has developed in Chittagong city within the last two decades. There is no much research work on cross elasticity of demand on wooden furniture of Chittagong city. The study attempts to know the effect of several selected factors on wooden furniture. It accomplishes with a semi-structured questionnaire and collects data from 150 households randomly. It hypothesizes that alternative products to wooden furniture are good substitutes. The study identifies that the wooden furniture as a relatively necessary product has an elasticity measurement of less than 1 concerning the alternative products. The cross elasticity of wooden furniture to its alternative products’ quantity is 0.30012 at a positive relationship (p